Legal Issues in Use of Nik to Purchase Train Tickets in Indonesia - Fausta, Andhika; Rafeyfa, Debby Nauli; Sukma, Nadira Fariza; Yayi Tarina, Dwi Desi (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The use of a National Identification Number (NIK) to purchase train tickets in Indonesia has become standard in transactions in the land transportation sector.  Although the aim is to strengthen passenger identity verification, its implementation raises various legal issues that need to be studied further. This article aims to analyze legal issues related to the use of NIK in purchasing train tickets, especially related to data privacy, consumer protection, and potential defaults in transportation services.  The use of NIK as passenger identity raises concerns about misuse and leakage of personal data, which could harm consumers. Apart from that, cases of default such as ticket cancellations and refunds also often occur, giving rise to legal disputes between consumers and companies providing transportation services. This analysis uses a juridical-normative approach by referring to applicable regulations, including the Personal Data Protection Law and regulations related to transportation. The results of this research indicate the need for increased regulation and supervision in the implementation of the NIK-based ticket purchasing system in order to protect consumer rights and prevent potential violations of the law.